Two-degree-of-freedom flow-induced vibration of two circular cylinders with constraint for different arrangements. (1st April 2021) - Zou, Qunfeng; Ding, Lin; Zou, Rui; Kong, Hao; Wang, Haibo; Zhang, Li
Abstract: The flow-induced vibrations (FIV) in two degrees of freedom for two circular cylinders with three arrangements including parallel, tandem, and stagger were investigated numerically, the rigid constraint is considered due to its widespread in industry fields. The effects of arrangement and constraint on FIV characteristics, including trajectory, vibration response, force response, and near wake structure, are analyzed. Results indicate that the existence of constraint can significantly suppress the vibration of the two cylinders when reduced velocity U *<7. However, when U *≥7, the oscillation of the parallel cylinders with constraint in cross-flow direction is strengthened. Moreover, the existence of constraint can reduce the vibration frequencies of cylinders with tandem arrangement significantly. The trajectory in the shape of "8" can be captured in most cases of motion for the cylinders without constraint. And the closed single-loop, "8", and "I" shape trajectories are obtained for the vibration of cylinders with constraint. The two cylinders move synchronously when the constraint is applied, and the near wake structures of the two cylinders are more stable than that without constraint. HIGHLIGHTS: Constraint can significantly suppress FIV when reduced velocity is less than 7. Amplitude of side-by-side cylinders with constraint is much higher than that without constraint. Closed single-loop, 8, and I shape trajectories can be observed for cylinders with constraint in FIV. Wake structure of cylinders with constraint is more stable than that without constraint.